2020
DOI: 10.1159/000512213
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Angiographic Geometry on the Clinical Presentation of True Vein of Galen Aneurysmal Malformations

Abstract: <b><i>Background Purpose:</i></b> Vein of Galen aneurysmal malformations (VGAM) may carry life-threatening and catastrophic sequelae in children. Their clinical presentations are differently variable between cardiac and cerebral syndromes. There may be a possible relationship between the Galenic angioarchitecture and the clinical presentation. We aimed to study the effect of the venous outflow impairment on the incidence of high-flow heart failure and the incidence of hydrocephalus. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Similarly, since neonates with VOGM have altered brain development and experience early neurologic injury, many functional neurologic outcomes may be unavoidable in such severe cases. For example, one study showed that a high degree of stenosis (>70%) of the draining sinus was significantly associated with VGAM aneurysmal enlargement and occurrence of hydrocephalus (65). Hemodynamic abnormalities in-utero could also cause hypoxic brain injury prior to endovascular embolization, leading to worse outcomes in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, since neonates with VOGM have altered brain development and experience early neurologic injury, many functional neurologic outcomes may be unavoidable in such severe cases. For example, one study showed that a high degree of stenosis (>70%) of the draining sinus was significantly associated with VGAM aneurysmal enlargement and occurrence of hydrocephalus (65). Hemodynamic abnormalities in-utero could also cause hypoxic brain injury prior to endovascular embolization, leading to worse outcomes in neonates.…”
Section: Discussionmentioning
confidence: 99%